Effect of metabolizable protein intake on growth performance, carcass characteristics, and feeding behavior in finishing steers - Sitorski, Leonardo G (Transl Anim Sci, 2019)
One-hundred thirty-two finishing steers (300 ± 2.7 kg body weight [BW]) predominately of Angus, Simmental, and Shorthorn breeding were used to study the effect of metabolizable protein (MP) intake on growth performance, carcass characteristics, and feeding behavior. Steers were stratified by initial BW across five pens and randomly assigned to one of four dietary treatments to supply an average of 626, 906, 1,209, and 1,444 g MP/d (n = 33 per treatment). Feed intake and feeding behavior were measured using radio frequency identification tags and the Insentec feeding system. For feeding behavior, a visit was defined as each time the Insentec system detected a steer at the feed bunk. A meal was defined as eating periods by intervals no longer than 7 min. Steers were fed until they reached an average BW of 598 ± 3.1 kg. Average daily gain (ADG) responded quadratically (P < 0.01) with ADG increasing in steers fed 906 g MP/d and plateauing thereafter. Dry-matter intake (DMI; kg) responded quadratically (P = 0.009) with DMI increasing with MP intake up to 1,209 g/d MP and decreasing thereafter. Gain to feed ratio (G:F) increased linearly (P = 0.04) and tended (P = 0.10) to respond quadratically, as G:F increased up to 906 g MP/d and plateaued thereafter. A quadratic response (P = 0.04 and P = 0.02, respectively) was observed for marbling score and 12th rib subcutaneous fat thickness with steers fed 1,209 g MP/d having the greatest marbling score and back fat thickness. A quadratic effect for visits and meals per day was observed (P < 0.01) with steers fed the 1,209 g MP/d treatment having the least visits and meals per day. In addition, time eating per visit responded quadratically (P = 0.05) with time increasing from 626 to 906 g MP/d. There was a linear increase (P ≤ 0.02) in time eating per meal and per day with increasing MP intake. A quadratic effect (P < 0.03) was observed for DMI per visit, meal, and minute with steers fed 1,209 g MP/d having the greatest DMI. In summary, steers fed 626 g MP/d had increased visits and meals per day. However, DMI per visit, meal, and minute were greater in steers fed 1,209 g MP/d. A day × treatment interaction (P < 0.001) was observed for plasma urea N as concentrations increased to a greater extent over time in the higher MP treatments than in the lower MP treatments. These data indicate that MP supply (from deficient to excess) influences growth performance, carcass characteristics, and feeding behavior of finishing steers.